Étude de l'Activité Antibactérienne synergique de la Résine d'Oliban et du Citrus aurantiifolia : Exploration des Mécanismes et Applications Potentielles en Microbiologie." - CHIGUER, kheira (My University, 2024)
In a context where antibiotic resistance is becoming an increasing concern, the search for alternative and sustainable solutions to combat bacterial infections has become essential. Natural plant extracts, rich in bioactive compounds, are garnering growing interest due to their potential antimicrobial properties. This study aims to evaluate the antibacterial activity as well as the content of polyphenols and flavonoids in three aqueous extracts: Boswellia resin, Citrus aurantiifolia peel, and their combination. Polyphenols were quantified using the Folin-Ciocalteu method and flavonoids using the aluminum trichloride method. The assessment of antibacterial activity was conducted using the well diffusion method. Results revealed that the combination of lime peel and frankincense resin exhibited the highest concentration of polyphenols and flavonoids, as well as the largest inhibition zone against a range of pathogenic bacteria, including E. coli, S. aureus, P. aeruginosa, B. cereus, and C. albicans. These findings suggest a synergy between the extracts, enhancing their antibacterial activity. Overall, this study highlights the promising potential of the combination of frankincense resin and lime peel as a natural alternative to traditional antibiotics, paving the way for optimization of formulations and development of new pharmaceutical and veterinary products.